2006
DOI: 10.1051/forest:2006069
|View full text |Cite
|
Sign up to set email alerts
|

Tree nutrition of Norway spruce as modified by liming and experimental acidification at the Höglwald site, Germany, from 1982 to 2004

Abstract: -From 1982 to 2004 the elemental concentrations of current, current+1, and current+2 year old needles of a mature spruce stand were investigated at the N-saturated, acidified, but healthy Höglwald site. The control was compared with a liming, experimental acid irrigation, acid irrigation + liming, normal irrigation, and normal irrigation + liming treatment. Liming was performed in 1984, and irrigation from [1984][1985][1986][1987][1988][1989][1990]. High year to year variations were found for most of the eleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 35 publications
2
15
0
4
Order By: Relevance
“…exhibiting no symptoms of defoliation (Farrell et al 1996;Huber et al 2004a). The mean yearly increment of the trees was similar (Table 1), and foliar analysis indicated good nutrition of the major elements (Table 2; Huber et al 2006a). Litterfall fluxes at HW were higher for most of the elements due to higher litterfall mass (Table 2), while the concentrations of P, Mg and Na were higher at BH (see Table 2).…”
Section: Site Descriptionsmentioning
confidence: 93%
See 1 more Smart Citation
“…exhibiting no symptoms of defoliation (Farrell et al 1996;Huber et al 2004a). The mean yearly increment of the trees was similar (Table 1), and foliar analysis indicated good nutrition of the major elements (Table 2; Huber et al 2006a). Litterfall fluxes at HW were higher for most of the elements due to higher litterfall mass (Table 2), while the concentrations of P, Mg and Na were higher at BH (see Table 2).…”
Section: Site Descriptionsmentioning
confidence: 93%
“…At the study plots, NO 3 -leaching was observed over [20 years at HW and periodically at BH prior to clear cut; the soil C:N ratio at both plots was close to the threshold of 30, below which there is potential for NO 3 -leaching. Moreover, both mature stands exhibited optimal N nutrition in current needles (see Table 2 and Huber et al 2006a). According to Aber et al (1998), N 2 O emission is a sign of N saturation; very high N 2 O emission was observed at HW, and both emission and deposition of N 2 O were also observed at BH (Butterbach-Bahl et al 1998), suggesting that BH was close to or at the beginning of N saturation.…”
Section: Nitrate Leachingmentioning
confidence: 94%
“…It was reported that lime application had no effects on loblolly pine after 20 years (Torbert and Burger 1984) and Norway spruce and beech after 40 years (Persson et al 1995). Huber et al (2006) noted that liming had a relatively insignificant effect on the needle chemistry.…”
Section: Discussionmentioning
confidence: 99%
“…forest at the Höglwald (Bavaria, Germany), which has been a long term ecological monitoring and experimentation site for more than 20years (Huber et al 2005) with focus on biogeochemistry and ecosystem research. For more detailed information about the stand and site characteristics see Kreutzer and Bittersohl (1986), Göttlein and Kreutzer (1991), Kreutzer (1995), Kreutzer and Weis (1998), Gessler et al (1998), Butterbach-Bahl et al (1998, 2002b, Rothe et al (2002), Huber et al (2004aHuber et al ( , b, 2005Huber et al ( , 2006. The site is exposed to high loads of atmospheric N deposition via throughfall of about 30kg N ha −1 year −1 under spruce (Rothe et al 2002) and has been shown to be a significant source for NO and also for N 2 O (Butterbach-Bahl et al 2002a).…”
Section: Study Sitementioning
confidence: 98%